Correlation Coefficients of Consistency of Single Valued Neutrosophic Set for Design Optimization and Quality Metrics in the Development of Multifunctional Clothing Systems - Li Zhang; Wei Su (Neutrosophic Sets and Systems)
The evolution of wearable technology and increasing consumer demand for versatile apparel have catalyzed the emergence of multifunctional clothing systems. These garments integrate features such as thermal regulation, smart sensor integration, environmental protection, and modular design to serve multiple purposes across different contexts. This study aims to evaluate the design optimization and quality metrics necessary for the development of such clothing systems, using uncertainty framework. Six criteria ranging from material sustainability to smart feature integration were assessed across six alternative clothing prototypes. The study applied systematic evaluation techniques to quantify and rank the design options based on performance, comfort, and innovation. This study proposes a methodology to convert the neutrosophic multivalued set (NMVS) into a consistency single valued neutrosophic set (CSVNS) using the averages values and consistency to obtain correlation coefficients. Results demonstrate the significance of aligning user-centered design principles with technological advancements in textile engineering. This research contributes to the structured development of multifunctional clothing, guiding designers and manufacturers toward smarter, more adaptive solutions.